Assessment of High School Principal’s Transformational Leadership - Nahiyah Jaidi Faraz (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2011)
Abstract The purposes of the study are to analyze: (1) characteristic of strategic partner and change agent roles, talent management and managers performance, (2) influence of strategic partner and change agent roles to talent management and its impact to managers performance. Four hundred hotel managers in Bali were participated in this study by using proportional random sampling. Data were analyzed using descriptive analysis and SEM. The result shows that: (1) strategic partner and change agent role, talent management and managers performance are in enough category, (2) positive and significant effect between strategic partner and change agent roles to talent management and its impact to managers performance. Keywords:Strategic Partner Role, Change Agent Role, Talent Management, Managers Performance.AbstrakTujuan penelitian ini adalah untuk menganalisis: (1) karakteristik dari mitra strategis dan peran agen perubahan, manajemen bakat dan kinerja manajer, (2) pengaruh mitra strategis dan peran agen perubahan untuk manajemen bakat dan dampaknya terhadap kinerja manajer. Sebanyak empat ratus manajer hotel di Bali berpartisipasi dalam penelitian ini dengan menggunakan proporsional random sampling. Data dianalisis menggunakan analisis deskriptif dan SEM. Hasil penelitian menunjukkan bahwa: (1) mitra strategis dan peran agen perubahan, manajemen bakat dan kinerja manajer termasuk dalam kategori cukup, (2) pengaruh positif dan signifikan antara mitra strategis dan peran agen perubahan untuk manajemen bakat dan dampaknya terhadap kinerja manajer.Keywords: Peran Mitra Strategis, Peran Agen Perubahan, Manajemen Talenta, kinerja Manajer.